Transfiguration of discarded PVDF ultrafiltration membranes Optimization of pyrolysis parameters for high-value char production - Pereira da Silva, Isabel (Waste management (New York, N.Y.), 2024)
Copyright © 2024 Elsevier Ltd. All rights reserved.